Pembinaan Keagamaan Berbasis Kajian Fikih Dan Akidah Bagi Warga Binaan Untuk Persiapan Reintegrasi Sosial - Ali Mutashom; Fadli Aziz; Fazar Sodik (SIGMA : Jurnal Sinergi Mengabdi, 2026)
Religious guidance in correctional institutions has a strategic role in preparing inmates for social reintegration after release. However, many inmates still lack adequate understanding of fiqh and aqidah, necessitating a structured and sustainable guidance program. This community service activity aims to enhance understanding of fiqh and aqidah, strengthen spiritual and moral awareness, and develop positive mindsets among inmates as a preparation for social reintegration. The method employed is Participatory Action Research (PAR) with a qualitative descriptive approach, implemented through halaqoh sessions and classical studies on a scheduled basis. The material provided covers the study of fiqh ibadah (thaharah, prayer, fasting) and aqidah (identity in belief, aqidah 50, and moral values). Data collection techniques used unstructured interviews and documentation. The results indicate an improvement in inmates' understanding of fiqh and aqidah, reflected in changes in their perspective on worship and awareness of aqidah as the foundation of behavior. Furthermore, inmates began to demonstrate discipline in worship, mutual respect, and internal motivation to become better individuals. This activity also provides strategic benefits in preventing recidivism and preparing inmates mentally and spiritually to return to society. Thus, religious guidance based on the study of fiqh and aqidah not only serves as a means of spiritual rehabilitation but also as an essential foundation for the successful social reintegration of inmates at Class I Correctional Facility Kesambi Cirebon.